Designing a Risk-Based Review Plan for Accrual Based Local Government Financial Reports - Fira Chairunnisa; Bambang Pamungkas (AFEBI Accounting Review, 2020)
The application of Accrual-Based Government Accounting Standards (SAP) since 2015 still causes problems including misstatement in Local Government Financial Reports (LKPD). The role of the Inspectorate in minimizing these problems is manifested in conducting a review of LKPD. Preliminary research shows that the implementation of LKPD review in Bandung District has not been effective in detecting financial statement misstatements. This study aims to evaluate and design a risk-based review plan on accrual-based LKPD at the Bandung District Inspectorate, and also expected to be a guideline for Regional Government Inspectorates in planning LKPD reviews to generate government financial reports in accordance with SAP. This study uses a case study approach with qualitative methods. The results of the study show that the LKPD review planning at the Bandung District Inspectorate has been carried out according to regulations and IIA standards, but there are weaknesses at the stage of entity's understanding and risk identification. The design of review procedures that have not implemented a risk-based approach also has an impact on an ineffective review, therefore in this study a risk-based LKPD review plan was designed. The output of this review plan will contain testing procedures in accordance with the risk areas of the financial statements.